THE SIMULATION OF UNMANNED AERIAL VEHICLE EAGLE-X AS SPARROWS PESTS REPELLENT - Retnowati, Nurcahyani Dewi; Junaidin, Buyung; Dasrial, Dasrial (Vortex, 2022)
The technology that can be developed from Unmanned Aerial Vehicle (UAV) in agriculture is the Unmanned Aerial Vehicle Eagle-X. This technology can help farmers in carrying out their daily activities to repel bird pests on agricultural land. However, people have difficulty understanding how to use UAVs. So, with this simulation, it is hoped that it can help farmers and producers understand the workings of the eagle-x aircraft. The simulation is made using 3Ds Max software which functions to create all 3D objects and also uses Unity software to create animations and simulations. This simulation can run well on a PC or laptop that has a Windows 10 operating system with 64bit and a minimum of core i-3 specifications.  Trials using simulations were carried out on 30 farmers and the results showed that 86.67% of farmers stated that this simulation was effective in providing an overview of how the Unmanned Aerial Vehicle Eagle-X works in repelling sparrow pests.